2011
DOI: 10.1371/journal.pcbi.1002205
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Spatiotemporal Dynamics of the 2009 H1N1 Pandemic in Europe: Implications for Real-Time Modelling

Abstract: Influenza pandemics in the last century were characterized by successive waves and differences in impact and timing between different regions, for reasons not clearly understood. The 2009 H1N1 pandemic showed rapid global spread, but with substantial heterogeneity in timing within each hemisphere. Even within Europe substantial variation was observed, with the UK being unique in experiencing a major first wave of transmission in early summer and all other countries having a single major epidemic in the autumn/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
145
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(163 citation statements)
references
References 39 publications
16
145
1
1
Order By: Relevance
“…An example is epidemic modelling, where spatially structured and agent-based models at various granularities (country, inter-city, intra-city) have been pushed to the computational limits with the integration of huge amount of data describing the flows of people and/or animals [93][94][95][96][97] . These models can generate results at an unprecedented level of detail and have been used successfully in the analysis and anticipation of real epidemics, such as the 2009 H1N1 pandemic 98,99 . Computer simulations thus become valuable in allowing both in silico experiments that would be infeasible in real systems and the capability to analyse and forecast scenarios.…”
Section: Reaction-diffusion Processes and Computational Thinkingmentioning
confidence: 99%
“…An example is epidemic modelling, where spatially structured and agent-based models at various granularities (country, inter-city, intra-city) have been pushed to the computational limits with the integration of huge amount of data describing the flows of people and/or animals [93][94][95][96][97] . These models can generate results at an unprecedented level of detail and have been used successfully in the analysis and anticipation of real epidemics, such as the 2009 H1N1 pandemic 98,99 . Computer simulations thus become valuable in allowing both in silico experiments that would be infeasible in real systems and the capability to analyse and forecast scenarios.…”
Section: Reaction-diffusion Processes and Computational Thinkingmentioning
confidence: 99%
“…Individuals are considered to be in contact with other members of their workplace during the day and with other household members during the night. In recent years, modelers have successfully expanded the large scale Agent Based approach to the country [6] and even continent level [56].…”
Section: Agent-based Modelsmentioning
confidence: 99%
“…With these findings in mind, the main practical inference of this study is that further longitudinal research incorporating prospective evaluations of actionable alerts (Milinovich et al 2014) is required before eHealth data sources can be used as influenza monitoring tools in routine public health practice. Following this conclusion, a meta-narrative review was conducted in which two narratives for reporting prospective evaluation of influenza detection and prediction algorithms were identified.…”
Section: Discussionmentioning
confidence: 99%
“…The findings were promising and corresponded to the recent outcomes worldwide (Kim et al 2013, Timpka et al 2014a, Nagel et al 2013, Yom-Tov et al 2014, Kirian & Weintraub 2010, Socan et al 2012). However, it was concluded that further longitudinal research incorporating prospective evaluations of actionable alerts (Milinovich et al 2014) is required before eHealth surveillance systems can be used in routine public health practice. For that reason, in this thesis, both existing methods and the nowcasting method were applied to prospective syndromic data and naturally also to traditional influenza data.…”
Section: Data Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation